Evaluation of IgG, IgM, CD4+ and CD8+ T cells during neoadjuvant chemotherapy with Tezio and Apatinib in gastric cancer patients - Cui, Zhe; Zhang, Jianjun; Zhang, Jing; Xu, Lan (Cellular and Molecular Biology, 2020)
This experiment was carried out to study the effect the neoadjuvant chemotherapy with Tezio and Apatinib on the treatment of advanced gastric cancer and its impact on the postoperative immune function of patients’ function. The patients with advanced gastric cancer who were treated in gastrointestinal surgery in our hospital from January 2017 to December 2018 were divided into two groups. The new chemotherapy and the traditional chemotherapy groups. The new chemotherapy group received neoadjuvant chemotherapy of Tezio combined with Apatinib before surgery, and the control group received the traditional first-line chemotherapy regimen of oxaliplatin combined with capecitabine. During the chemotherapy, the adverse complications of the two groups of patients were recorded, and the RECIST1.1 evaluation system was used to evaluate the chemotherapy effect of the patients after chemotherapy. At the same time, the R0 resection rate of the two groups of patients with gastric cancer radical surgery was recorded and compared. The fasting venous blood of the patients was collected before the chemotherapy, after the end of chemotherapy, and one week after the operation. The content of immunoglobulin G and M (IgG and IgM) was measured. The flow cytometry was used to detect CD4 + T cells and CD8+ T cells. A total of 64 patients were enrolled in this study, including 26 patients in the new chemotherapy group. Chi-square test showed that the incidence of bone marrow suppression (Leukopenia, thrombocytopenia and anemia) and liver dysfunction in the new chemotherapy group were lower than that in the traditional chemotherapy group (all P <0.05), but the surgical R0 resection rate in the new chemotherapy group was higher than that in the traditional chemotherapy group (P <0.05). Wilcoxon rank-sum test and chi-square test found that the chemotherapy effect of the new chemotherapy group was better than that of the traditional chemotherapy group, and the results of repeated measures analysis of variance showed that the IgG, IgM and CD4+/CD8+ T cell ratios of the patients in the new chemotherapy group were higher than that of traditional chemotherapy group (all P <0.05). Apatinib combined with Tezio’s preoperative neoadjuvant chemotherapy can improve the chemotherapy effect of advanced gastric cancer, increase the rate of surgical R0 resection, and reduce the patient’s immunosuppressive status during treatment.